SVP: Sinusoidal Viewport Prediction for 360-Degree Video Streaming - Xiaolan Jiang (IEEE Access, 2020)
The rapid growth of user expectations and network technologies has proliferated the service needs of 360-degree video streaming. In the light of the unprecedented bitrates required to deliver entire 360-degree videos, tile-based streaming, which associates viewport and non-viewport tiles with different qualities, has emerged as a promising way to facilitate 360-degree video streaming in practice. Existing work on viewport prediction primarily targets prediction accuracy, which potentially gives rise to excessive computational overhead and latency. In this paper, we propose a sinusoidal viewport prediction (SVP) system for 360-degree video streaming to overcome the aforementioned issues. In particular, the SVP system leverages 1) sinusoidal values of rotation angles to predict orientation, 2) the relationship between prediction errors, prediction time window and head movement velocities to improve the prediction accuracy, and 3) the normalized viewing probabilities of tiles to further improve adaptive bitrate (ABR) streaming performance. To evaluate the performance of the SVP system, we conduct extensive simulations based on real-world datasets. Simulation results demonstrate that the SVP system outperforms state-of-the-art schemes under various buffer thresholds and bandwidth settings in terms of viewport prediction accuracy and video quality, revealing its applicability to both live and video-on-demand streaming in practical scenarios.